Titulación de tierras rurales y derechos de propiedad: legislar a las peque\~nas propiedades rurales como bienes de familia inembargables mejora el bienestar de los peque\~nos productores familiares? - Juan M. Murguia; Kassu W Hossiso; Sergio H. Lence (Inter-American Development Bank (IDB), 2019)
– Land titling and property rights have been the central tenant of agricultural and rural development policy for many years since land is one of the key assets for production of agricultural goods and services. Land titling facilitates access to credit through collateral arrangement,thereby induces on-farm investment and improves agricultural productivity. This paper evaluates a particular policy in Bolivia, where legislation limits legally defined smallholding's farm and ranch lands from being used as collateral, in order to prevent small landowners from selling out their land in response to temporary shocks and safeguarding smallholders' source of income, avoiding the seizure of their assets. This study analyzes the effect of this policy on land prices, to investigate whether smallholders' welfare is improved by this protective measure or not, assessing if the positive impact of the land risk premium generated by the non-seizability, has a bigger effect than the negative impact of the capital constraint reducing optimal investment. Differences in land prices are assumed to reflect differences in expected future profits, thereby used as a measure of welfare. We use a unique dataset of 2,609 recorded land transactions in the Department of Santa Cruz, Bolivia, during the period between 2010 and 2015 to determine whether being a smallholding affects land price per hectare. We refine our analysis considering small neighborhood variations near the cutoff value for 'small farms' and 'small ranches' to account for other unobservable exogenous factors affecting land prices other than non-seizability. Results indicate that the effects are heterogenous among the classifications of farms and ranches. The price of ranch lands is negatively associated with the legal definition of 'small' ranch, implying that the negative effect of capital constraint dominates the positive effect of land risk premium, while the opposite is true for farm lands- land prices are higher for 'small-holdings'. Our findings have important policy implications, and the potential to increase their efficiency, for instance a plausible option would be the implementation of differentiated land legislation policies given the type of land, and another would be to allow farmers and ranchers to self-select into the legal classifications of land, which could potentially improve the welfare of those negatively affected by the restriction.
Keywords: Q12; Q15; 330; Bolivia; Land titling; Property Rights; Smallholders